Pengolahan dan Pemanfaatan Buah Merah dalam Upaya Pengentasan Kemiskinan - Bhaskara Anggarda Gathot Subrata; Agus Sumaryadi; Girinius Wenda (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Processing and utilization program of red fruit in Yiwika Village are based on the reality that the people of Yiwika Village still cannot escape from the poverty. One of the great untapped potentials in Yiwika Village is the red fruit. Therefore, the solution offered is the processing and utilization of red fruit to be processed products. The purpose of this program is to provide knowledge and skills to the people of Yiwika Village in processing red fruits into oil and red fruit jams in order to create a red fruit processed fruit management with a good and sustainable system of management and increased its economy. Methods to solve these problems through problem identification, program socialization, training of Community Organization Management, evaluation and reflection. The program was implemented in September 2017 in Yiwika Village, Kurulu District, Jayawijaya Regency. The team has succeeded in bringing an important change to the society that is changing the paradigm of people from selling red fruit directly to processing red fruit into oil and red fruit jam.